Model pomiaru cechy ukrytej na podstawie wskaźników dychotomicznych - Bartkowiak, Anna (Latent Variable Model for Binary Data, 2006)
Latent variable is a variable which is not directly observable. To measure this kind of variable we need a observable indicators. Latent and observable variable are bound by some function. In literature there are many methods to analyze latent variable model. This article discusses on one of this methods intended for continuous latent variable and binary data (observable variables). One-factor model logit it shown to fit as latent variable model. The method is illustrated by one empirical example.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 98-110